Neutrophil-Derived Cytokines: Facts Beyond Expression - Tecchio, Cristina; Micheletti, Alessandra; Cassatella, Marco A. (Frontiers in Immunology, 2014)
Polymorphonuclear neutrophils, besides being involved in primary defense against infections – mainly through phagocytosis, generation of toxic molecules, release of enzymes and formation of extracellular traps - are also gaining importance as cells contributing to finely regulate the development of inflammatory and immune responses. These latter functions of neutrophils occur, in part, via their de novo production and release of a large variety of cytokines, including chemotactic cytokines (chemokines). Accordingly, the improvement of technologies for molecular and functional cell analysis, along with concomitant advancing in cell purification techniques, have allowed the identification of a continuously growing list of neutrophil-derived cytokines, as well as the characterization of their biological implications in vitro and/or in vivo. This short review summarizes crucial concepts on the modalities of expression, release and regulation of neutrophil-derived cytokines. It also highlights examples illustrating the potential implications of neutrophil-derived cytokines according to recent observations made in humans and/or in experimental animal models.